As implicações das teorias de Vygotsky na educação: a mediação no pocesso do desenvolvimento infantil - Nobukuni, Aline Regina Migose [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The present monograph results from a bibliographical research, which takes into account the Historical-Cultural Psychology, and aims to study the theoretical propositions of Lev Semenovich Vygotsky (1896-1934) about mediation and its relation to human development, in order to analyze the reflexes of their studies in education. Therefore, some works were selected so we could organize this work. Initially, we did some exploratories readings about the subject, among them, we highlight the authors: Newton Duarte, Lígia Martins, Teresa Rego and Vygotsky. Taking into account the Marxist influences of Vygotsky and the fact that he is a Soviet philosopher, we went through a short way that led us to the historical-cultural theory, which comprises a man as an individual that develops biologically but also socially. In this study, we focus on the development process of this person in the social environment, and how the mediated activity, imitation and the role of the mediating adult are important. In the midst of this process, we approach a conception of extreme importance in Vygotsky's studies: The zone of proximal development. We started from it and from other postulates to explain Vygotsky's contributions in education, for example, the appreciation of the idea that the subjects should be organized according to the knowledge of each stage reached by the development of the child, not discarding this knowledge, but pretending that the contents present in schools are linked to what has not yet been formed in the learner

A presente monografia resulta de uma pesquisa bibliográfica, que leva em consideração a Psicologia Histórico-Cultural, e tem por objetivo estudar as proposições teóricas de Lev Semenovich Vygotsky (1896-1934) acerca da mediação e de sua relação com o desenvolvimento humano, a fim de analisar os reflexos de seus estudos na educação. Para tanto, algumas obras foram selecionadas para que pudéssemos organizar o trabalho. Inicialmente, fizemos algumas leituras exploratórias sobre o assunto, dentre elas, destacamos os autores: Newton Duarte, Lígia Martins, Teresa Rego e Vygotsky. Levando em consideração as influências marxistas de Vygotsky e o fato de ser um filósofo soviético, percorremos um breve caminho que nos levou a teoria histórico-cultural, que compreende o homem como indivíduo que se desenvolve de forma biológica, mas também social. Por meio disso, tratamos neste estudo em focar o processo de desenvolvimento desse indivíduo no meio social e como a atividade mediada, a imitação e o papel do adulto mediador são importantes. Em meio a esse processo, abordamos uma concepção de extrema importância nos estudos de Vygotsky: A zona de desenvolvimento proximal, e partimos dela e de outros postulados, para explicar as contribuições de Vygotsky na educação, como por exemplo, a valorização da ideia de que as matérias devam ser organizadas de acordo com o conhecimento de cada etapa atingida pelo desenvolvimento da criança, não descartando esse conhecimento, mas pretendendo que os conteúdos presentes nas escolas sejam vinculados àquilo que ainda não foi formado no educando
Keywords: Vigotsky, L. S. (Lev Semenovich), 1896-1934; Psicologia; Mediação; Educação; Crianças - Desenvolvimento; Child development